Bridging the Educational Gap: The Role of Digital Learning Platforms in Developing Countries - Win Min Zaw; Su Su Hlaing (International Journal of Educational Development, 2024)
This study examines the role of digital learning platforms in improving educational access and quality in developing countries. By reviewing case studies of online education initiatives, the research evaluates how digital platforms address common barriers such as teacher shortages, limited resources, and geographic isolation. Findings reveal that digital learning enhances educational equity, especially when supported by proper infrastructure and training for educators and students. The paper highlights key strategies for maximizing the potential of digital learning in resource-constrained environments.